Analisis Beberapa Faktor yang Mempengaruhi Ekspor Kerajinan Provinsi Bali dan Peramalannya - Sonia, Ni Putu Inneke; Sudirman, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 3, Maret 2015 (pp. 139 - 219), 2015)
Import-export activities are very important for the economy of a country. Export is the most profitable activity due to the country's foreign reserves could add, such as export activities of the craft in the province of Bali. The purpose of this research is to know the influence of tourists visit, inflation, investment, and exchange rate Dollar United States simultaneously and partial towards the export of handicrafts Bali province 1990-2013. Use the Data in this study is secondary data obtained from the Department of trade and industry of Bali, Bali province, Central Bureau of statistics, capital investment Coordinating Agency (BKPM) of Bali, Indonesia and Bank as well as related literature-literature and supporting this research.The research on analysis techniques using multiple regression analysis, VAR, and forecaset by using stata. The results obtained that tourists visit, investment, inflation, and the United States Dollar exchange rate effect simultaneously against the export of handicraft while partially, United States Dollar exchange rate and inflation affect negatively and significantly to export Handicrafts. Forecasting results obtained for the next two years is handicrafts export has decreased and tourists has increased.
Keywords: handicraft exports , tourist arrivals , inflation , investment , dollar exchange rate